Telemedicine technologies big data, deep learning, robotics, mobile and remote applications for global healthcare - Hemanth, D. Jude 1981-; Balas, Valentina E. 1956- (Academic Press, an imprint of Elsevier, 2019)
Telemedicine Technologies: Big Data, Deep Learning, Robotics, Mobile and Remote Applications for Global Healthcare illustrates the innovative concepts, methodologies and frameworks that will increase the feasibility of the existing telemedicine system. The book also focuses on showcasing prototypes of remote healthcare systems, thus emphasizing the data processing side that is often recognized as the backbone of any telemedicine system. - Illustrates the innovative concepts, methodologies and frameworks that will increase the feasibility of the existing telemedicine system- Focuses on showcasing prototypes of remote healthcare systems